Students' voices about information and communication technology in upper secondary schools. Issue 2 (5th March 2018) - Olofsson, Anders D.; Lindberg, Ola J.; Fransson, Göran
Abstract : Purpose: The purpose of this paper is to explore upper secondary school students' voices on how information and communication technology (ICT) could structure and support their everyday activities and time at school. Design/methodology/approach: In all, 11 group interviews were conducted with a total of 46 students from three upper secondary schools. NVivo PRO 11 was used for a qualitative content analysis. Findings: The results show that ICT plays a central role in the students' schooling, not in terms of "state-of-the-art" technology, but rather as "state-of-the-actual", by for example supporting the writing process and for peer support, digital documentation and storage. Research limitations/implications: A relatively small number of students in three schools and three specific programmes make generalisations difficult. Practical implications: Students' perspectives on the "state-of-the-actual" could influence teachers' use of ICT in education, their professional development activities and the development of an in-school ICT infrastructure. Social implications: The study could lead to a better understanding of students' expectations and use of ICT at school and in everyday life. Originality/value: The originality of this paper is the focus on students' voices about how the basic use and functionality of ICT could structure and support their everyday activities at school.